Relationship between Self-Esteem and Academic Engagement among Adolescents at Secondary School Level - Dr. Munwar Bagum; Qamar-un-Nisa; Dr. Sadia Jamil; Iqra Batool; Dr. Muhammad Javed Aftab; Dr. Asma Islam* (Al-Qanṭara, 2022)
Self-esteem is a life skill that is highly appreciated. In order to engage effectively in society, people must first evaluate them and then acquire the knowledge, abilities, and attitudes necessary. The major purpose of this study was to investigate the “self-esteem and academic engagement among adolescents”. The research was conducted at District Multan. The study focused on determining the relationship between self-esteem and academic engagement among adolescents’ students’ opinion’ at secondary school level. Researcher used the methodology regarding co-relational research and research tool was developed in questionnaire form with a five-point Likert scale to find results on the basis of findings and conclusion. A total of 3475 students’ sample was taken from target population after the analysis of data, it was found that Overall Academic Engagement among Adolescents and Overall Academic Engagement and Self Esteem Feelings having the linear relationship to each other’s. Similarly, it was also found from that both the factors self-esteem and academic engagement among adolescents having p-value less than the 0.05 which showed that it was significant. It was recommended Institutions should focus on making pleasant things useful – educational self-esteem and academic engagements process and promoting as a tool not only for communication and entertainment but also for learning.